Metodologi Tafsir Khuluqunm - Saadatul Jannah (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
Since the 16th century until the recent age, the study of exegesis is increasing significantly in Indonesia. This is marked by the spirit of producing commentaries from Indonesian scholars (pre-modern) such as works of Abd al-RaÅ«f al-SinkilÄ« (TarjumÄn al-MustafÄ«d), Syaikh NawawÄ« (Tafsir Marah LabÄ«d) and Ahmad SanusÄ« (Tafsir al-QurÄn al-KarÄ«m), and modern era explicitly Quraish Shihab (Tafsir al-Misbah) and Didin Hafidhudddin (Tafsir al-Hijri). On the other hand, Quranic exegesis is magnetizing the modern society, academia, and the government. Two things are a sign that Indonesia necessitates developing new outlooks contained in the works of interpretation, so the view of Indonesian society to be more extensive and varied without being limited by one of his Indonesian commentators. Yunan Yusuf, one of the Indonesian Muslim philosopher, within Tafsir Khuluqun 'AdzÄ«m endeavors coloring Indonesian elucidation by creating distinctive works that are an interpretation of the Koran from the short chapters (Madaniyah) to the extended chapters (Makiyah). This article discovers specifically the explanation of al-Mulk and depicts a qualitative method with the analytical comparative approach through the two references commentaries Indonesia Tafsir al-Azhar and al-Misbah. Yunan interprets the Koran critically and decisively with the color philosophy, and able to convey the message of the Qur'an through other verses in the Qur'an (munÄsabah al-QurÄn bi al-QurÄn).